2012
DOI: 10.1111/j.1526-4637.2012.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Perception in Schizophrenia: Evidence of a Specific Pain Response Profile

Abstract: Results indicate that schizophrenic subjects present a specific experimental pain response profile, characterized by elevated sensitivity to acute pain but reduced sensitivity to prolonged pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 44 publications
1
37
1
Order By: Relevance
“…Additionally, de la Fuente‐Sandoval et al ()) observed that drug‐naïve SCZ patients had a higher pain tolerance and a reduced activation in brain regions related to affective‐cognitive aspects of pain processing (insula and cingulate cortex) to thermal painful stimuli than HC. This pain insensitivity in SCZ patients was normally explained by a supra‐spinal mechanism involving bottom‐up and/or top‐down modulations in previous studies (de la Fuente‐Sandoval et al, ; Levesque et al, ; Potvin et al, ). For example, Levesque et al () observed that SCZ patients had a decreased sensitivity to prolonged pain, which was not accompanied by any difference in the nociceptive flexion reflex response.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, de la Fuente‐Sandoval et al ()) observed that drug‐naïve SCZ patients had a higher pain tolerance and a reduced activation in brain regions related to affective‐cognitive aspects of pain processing (insula and cingulate cortex) to thermal painful stimuli than HC. This pain insensitivity in SCZ patients was normally explained by a supra‐spinal mechanism involving bottom‐up and/or top‐down modulations in previous studies (de la Fuente‐Sandoval et al, ; Levesque et al, ; Potvin et al, ). For example, Levesque et al () observed that SCZ patients had a decreased sensitivity to prolonged pain, which was not accompanied by any difference in the nociceptive flexion reflex response.…”
Section: Discussionmentioning
confidence: 71%
“…This pain insensitivity in SCZ patients was normally explained by a supra‐spinal mechanism involving bottom‐up and/or top‐down modulations in previous studies (de la Fuente‐Sandoval et al, ; Levesque et al, ; Potvin et al, ). For example, Levesque et al () observed that SCZ patients had a decreased sensitivity to prolonged pain, which was not accompanied by any difference in the nociceptive flexion reflex response. To achieve better understandings of the supra‐spinal mechanism, we performed seed‐based RSFC analyses for thalamus and PAG, which are key nodes in the ascending and descending pain modulation pathways respectively.…”
Section: Discussionmentioning
confidence: 71%
“…Alterations in PUFA levels, therefore, could have wide-ranging effects both on neural functioning, inflammation, and any connections between the two. Abnormal pain reporting in schizophrenia has long been noted (Bonnot et al, 2009; Levesque et al, 2012), and eicosanoids could also be relevant in that domain. Interestingly, low levels of PUFAs in schizophrenia patients have been associated with negative symptoms (Bentsen et al, 2011; Bentsen et al, 2012), positive symptoms (Sumiyoshi et al, 2008), and poor cognition (Condray et al, 2008; Condray and Yao, 2011), indicating that they may be associated with pathology.…”
Section: Mechanismsmentioning
confidence: 99%
“…In line with a previous metaanalysis [43], we examined the funnel plot of the composite outcome searching for extreme outliers and removed from the database and all analyses one extreme publication bias outlier [39]. Across the resultant sample of 17 studies, we first conducted a composite analysis pooling aggregated pain measure data on pain threshold, pain tolerance and sensory threshold together from all studies to establish an overall difference in pain sensitivity.…”
Section: Meta-analysismentioning
confidence: 99%